Perbandingan jus kundur (Benincasa hispida) dan penggunaan gelatin terhadap mutu kimia dan organoleptik (jelly drink) - Farrell Ricardo Tirtasatya; Bambang Sigit Sucahyo; Yuyun Yuniati (University of Insan Cendekia Mandiri, 2025)
Kundur (Benincasa hispida) juice has health benefits and rich nutritional and medicinal properties, making it a potential ingredient for high-quality jelly drinks. This study aims to determine the optimal formulation of kundur juice and gelatin using a completely randomized design (CRD) with four treatments: P1 (80% kundur juice, 0.5% gelatin), P2 (80%, 0.7%), P3 (100%, 0.5%), and P4 (100%, 0.7%), and three repetitions. Parameters observed included vitamin C content, crude fiber, viscosity, and organoleptic attributes (taste, texture, color). The results showed that the best formulation was P1, with the highest acceptance of taste (3.7067), texture (3.5733), and color (3.6400), although the levels of vitamin C (4.64) and crude fiber (2.48) were lower than P4. Formulation P1 was considered the most suitable.